Perbedaan Pasta Gigi Deterjen Dengan Tanpa Deterjen Terhadap Penurunan Plak Skor Pada Siswa SMPN 1 Martapura Timur - Rolia Miftahul Nurilma Asura; Danan Danan (Jurnal Skala Kesehatan, 2021)
Caries is a dental problem that often occurs in developing countrieslike Indonesia. The cause of caries that occurs in the world's population is plaquei.e. 75% to 90%.Toothpaste used when brushing teeth serves to reduceplaque formation. Toothpaste is available in various types of contentone of them is sodium laury sulfate (SLS) (detergent) and enzymes (without detergent) as active substances. This study aims to determine whether there is a difference between toothpaste detergent with no detergent on the decrease in plaque scores in SMPN students1 East Martapura. The method used is a quasi-experiment with do pretest and posttest. The population is 178 people, taking sample by purposive sampling based on inclusion criteria as much as 60 people, with independent T-test. The results showed that there was a decrease in the average plaque score with respondents before brushing their teeth with detergent toothpaste was 2.47 after 2.00 with a difference of 0.47 and the average plaque score of respondents before brushing teeth with toothpaste without detergent by 2.64 after 1.96 with a difference of 0.71. Statistical test results = 0.039 <0.05. It was concluded that there was a difference between brushing teeth and toothpastedetergent with toothpaste without detergent. Recommended for SMPN 1 students East Martapura to better use toothpaste without detergent becausebetter at reducing plaque. Keywords: Detergent Toothpaste, Toothpaste Without Detergent, Plaque Score